Uruguay Round: further papers on selected issues (United Nations New YorkUS, 1990)
Addresses issues directly related to the Uruguay Round of trade negotiations. The range extends from the reforming of General Agreement articles on trade in agriculture to such issues as trade-related aspects of intellectual property rights, trade in services, and trade-related investment measures. Also considers a set of issues which are relevant in the context of the multilateral trading system. Examines the implications of some of the regional intergration measures by developed countries for third countries e.g. EC and United States - Canada Free Trade Agreement.
DC